Humanitarian Projects Development from Universidad del Zulia SIGHT Affinity Group - Luis Rodríguez; Javier Hernández; Javier Peres; José Viloria; Laura Sánchez; Henry Urdaneta; Douglimar González; Nardiz Mendoza; Josimar Tello-Maita; Andry Contreras; Manuel Briceño; Claudia Guevara (Tecnología en Marcha)
This work aims to divulge the volunteering experiences within humanitarian projects development from Universidad del Zulia SIGHT affinity group in Venezuela. At first, “Una mano por tu Facultad” project carried out in 2019 is described, which had the active participation of volunteers from the RE-IEEE-LUZ student branch and the SIGHT-LUZ affinity group and resulted in the recovery of twenty-six (26) classrooms and four (4) laboratories of the Faculty of Engineering. Furthermore, a new project is underway in response to COVID-19, which is focused on a distance education system using funds approved by the Humanitarian Activities Committee (HAC) and the Special Interest Group on Humanitarian Technology (SIGHT) of the Institute of Engineers Electrical and Electronic (IEEE). This group has the objective of bringing technologies-based solutions to problems existing in local communities in the Zulia State, Venezuela.